2019
DOI: 10.1186/s12891-019-2470-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcomes and implant survivorship after Total knee arthroplasty with the persona knee implant system: two year follow up

Abstract: Background More personalized implant designs for total knee arthroplasty might optimize the clinical outcome after surgery. One of these personalized implant designs is the Persona knee implant system (Zimmer Biomet, Warsaw, Indiana, USA). The primary objective of this study was to determine patient reported outcomes and implant survivorship of the Persona Knee system used in primary total knee arthroplasty, up to two years after surgery. Methods From November 2013 to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…An increase by more than the minimal clinically important difference (MCID) owing to its better correlation with clinical improvement is more important than a significant difference. The MCID of KSS is 34.5 points [20]. The mean improvement In the NMK group, there was a significant improvement in patients' Kujala score from preoperative to different stages of follow-up, and a similar trend was also observed in the MK group (P-value < .05).…”
Section: Discussionmentioning
confidence: 57%
“…An increase by more than the minimal clinically important difference (MCID) owing to its better correlation with clinical improvement is more important than a significant difference. The MCID of KSS is 34.5 points [20]. The mean improvement In the NMK group, there was a significant improvement in patients' Kujala score from preoperative to different stages of follow-up, and a similar trend was also observed in the MK group (P-value < .05).…”
Section: Discussionmentioning
confidence: 57%
“…The global burden of disease 2010 study showed that the global morbidity of symptomatic knee osteoarthritis was estimated to be 3.8%, and that the morbidity increases with age, and peaks at 50 years old [ 1 ]. TKA is currently proved to be an effective surgical method for patients with moderate or severe staged knee osteoarthritis and clinical practice has shown that it can significantly relieve the pain, improve the range of motion, increase the quality of life [ 2 , 3 ]. However, adverse events after TKA remain a severe challenge for surgeons, Postoperative complications such as venous thromboembolism (VTE), infection, periprosthetic fracture and dislocation have occurred in some patients [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, whether a high level of knee exion can be achieved with less cutting of the posterior femur bone than with the previous conventional model (NexGen-LPS-Flex® system (Zimmer Biomet, Warsaw, Indiana) remains to be elucidated [21]. To the best of our knowledge, only a few studies have reported short-term outcomes and no study has used this implant system in Asian knees [22,23]. Therefore, the primary aim of our study was to evaluate the clinical outcomes of the Persona® knee system including whether it could achieve a higher level of knee exion.…”
Section: Introductionmentioning
confidence: 99%